Rumpon Making Training for Local Fishermen in Hamadi Village, Jayapura City: Pelatihan Pembuatan Rumpon Bagi Nelayan Lokal di Kelurahan Hamadi Kota Jayapura - Rosye HR. Tanjung; Efray Wanimbo; Kalvin Paiki (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Rumpon is an environmentally friendly and highly effective fishing tool. Fishermen in the Jayapura city are skilled in capturing small pelagic fish, but they often have to search fish in constantly shifting and disorganized locations. This is due to a knowledge lack in determining the right fishing grounds. Another constraint is that Hamadi fishermen lack sufficient basic knowledge about the proper, correct, and environmentally friendly construction of rumpons. Factors influencing this situation include the lack of support from relevant agencies, limited knowledge, and the capital required for rumpon construction. Therefore, training in rumpon construction for fishermen in the Hamadi District is crucial. The aim of this training is to enhance the understanding of local fishermen in the city of Jayapura regarding the role of rumpons as fishing aids and environmentally friendly rumpon construction techniques. The methods used in this training include observation, the delivery of material on rumpon construction techniques, and focused group discussions (FGDs). From the results of the activities, local fishermen in the Hamadi District, Jayapura, have varying levels of understanding. However, based on the analysis, it is evident that the percentage of understanding among the fishermen before and after the training is significantly different. Before the training, the average level of understanding among fishermen was low in terms of rumpon construction steps. After the pre-test, about 60.625% of fishermen answered incorrectly, while only 39.375% answered correctly. However, after the training, a significant change occurred, with approximately 92.125% of fishermen answering correctly, and only about 7.875% answering incorrectly.